Efeito da adição de pó de Carboneto de silício nos fluidos dielétricos sobre o desempenho da usinagem por descargas elétricas do aço-rápido ABNT M2 - Fernandes, Luciano Antônio (1999)
There are some research in Electrical Discharge Machining that sought improvement in the material removal rate, tool wear ratio, quality of machined surfaces, dimensional and geometric accuracy of workpieces. Adding powder to the dielectric fluid can help to achieve these objectives. This work relates experiments carried out in modem EDM machine when rough cutting ABNT M2 high speed Steel. Three distinct commercial dielectric fluids, Silicon and Silicon Carbide powder, with several concentrations and grain sizes are used. It was investigated the effects on the material removal rate, tool wear ratio and two parameters related to the surface integrity: recast layer thickness and microhardness profile. The results show that when using kerosene as dielectric fluid, SiC powder gives better results than Si. When adding SiC powder (600 mesh) in a concentration of 30 g/l the followings results are obtained: great improvement in the material removal rate, increasing tool wear ratio, reduction of the recast layer thickness and none appreciable alteration in microhardness profile compared to fluid without powder.